A clinico-pathological study of benign breast diseases in rural population - Das, Narayan; Debbarma, Amarendra; Debbarma, Gautam (International Journal of Research in Medical Sciences, 2017)
Background:Objective of current study was to study the pattern of benign breast diseases in females in our society. Methods:One hundred females who were treated in the department of surgery at Agartala government medical college & G B P Hospital, Agartala, Tripura (West) with various forms of benign breast diseases during the period from January 2013 to December 2013, were studied. Diagnosis were made by a combination of clinical assessment, radiological imaging and tissue biopsy so - called triple assessment. Results:The commonest presentation of benign breast diseases was breast lump followed by nodularity of breast. Fibroadnomas are the commonest benign breast disease and fibrocystic changes form the second most common lesion. The common age group of benign breast diseases range from 21 years to 40 years. This might be associated with certain environmental, regional, dietary or hormonal factors. Conclusion:The result of this study showed that benign breast diseases in females of our society are fibroadenomas followed by fibrocystic diseases. The actual factors responsible for this change needs further research and study.